Analisis Kebijakan Perlindungan Anak Dari Tindak Pidana Perdagangan Orang Di Indonesia - Djorghi Samudra Triananda (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Children aged 0-18 years are still growing physically, mentally and intellectually. Children are at risk of violence and trafficking. To ensure the welfare of children, the rights and treatment of children must be guaranteed without discrimination. This research aims to describe legal protection for child victims of human trafficking crimes. This research uses a type of normative legal research. This research found that family economic factors, low education of children and families, as well as parents' negligence in taking care of children's administration such as birth certificates make it easier for child trafficking to occur because victims do not have an identity. According to Law no. 35 of 2014 concerning Child Protection, children as victims of human trafficking are protected from abuse and have dignity and human rights. Law no. 21 of 2007 concerning Eradication of the Crime of Human Trafficking and RPSA or Temporary Protection Homes for Children are other ways used by the Indonesian government to combat human trafficking.